PENGEMBANGAN MODEL E-LEARNING BERBASIS LMS-MOODLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Alan Suandra; Bambang Sahono (DIADIK, 2020)
The aims of this study to: (1) Creat e-learning based on LMS-Moodle to improve student learning outcomes.  (2) Improve students learning outcomes of Digital Simulation Subject of X Grade using e-learning model based on LMS-Moodle. In this study uses a development design (Research and Development).  The subjects of this study is students of Automotive Engineering Skills Competency of Vocational High School Number 02 Bengkulu City. The techniques of collecting the data uses the assessment sheets and student test results.  Data analysis used mean and t-test. The instrument of this study uses a Linkert scale. The conclusions of this research are; (1) The development of an e-learning model based on the LSM-Moodle can be used to improve student learning outcomes in digital simulation subject (2) The development of an e-learning model based on the LSM-Moodle can be feasible to improve learning outcomes of X Automotive Engineering grade at Vocational High School Number 02 Bengkulu City in digital simulation subject